A post-transcriptional program coordinated by CSDE1 prevents intrinsic neural differentiation of human embryonic stem cells. Issue 1 (December 2017) - Ju Lee, Hyun; Bartsch, Deniz; Xiao, Cally; Guerrero, Santiago; Ahuja, Gaurav; Schindler, Christina; Moresco, James; Yates, John; Gebauer, Fátima; Bazzi, Hisham; Dieterich, Christoph; Kurian, Leo; et al.
Abstract While the transcriptional network of human embryonic stem cells (hESCs) has been extensively studied, relatively little is known about how post-transcriptional modulations determine hESC function. RNA-binding proteins play central roles in RNA regulation, including translation and turnover. Here we show that the RNA-binding protein CSDE1 (cold shock domain containing E1) is highly expressed in hESCs to maintain their undifferentiated state and prevent default neural fate. Notably, loss of CSDE1 accelerates neural differentiation and potentiates neurogenesis. Conversely, ectopic expression of CSDE1 impairs neural differentiation. We find that CSDE1 post-transcriptionally modulates core components of multiple regulatory nodes of hESC identity, neuroectoderm commitment and neurogenesis. Among these key pro-neural/neuronal factors, CSDE1 binds fatty acid binding protein 7 (FABP7 ) and vimentin (VIM ) mRNAs, as well as transcripts involved in neuron projection development regulating their stability and translation. Thus, our results uncover CSDE1 as a central post-transcriptional regulator of hESC identity and neurogenesis. Unlike transcriptional regulation of hESC identity, little is known post-transcriptionally. Here, the authors show that the RNA binding protein CSDE1 regulates core components of hESC identity, neurectoderm commitment and neurogenesis to maintain pluripotency and prevent neural differentiation.